Answer:
[tex]\boxed {y - 1 = 2 (x + 7)}[/tex]
Step-by-step explanation:
First use the Slope Formula to determine the slope of two points:
[tex]m = \frac{y_{2} - y_{1}}{x_{2} - x_{1}}[/tex]
(Where [tex](x_{1}, y_{1})[/tex] is the first point and [tex](x_{2}, y_{2})[/tex] is the second point)
-Apply the two following points for the formula:
[tex](x_{1}, y_{1}) = (-7, 1)[/tex]
[tex](x_{2}, y_{2}) = (-3, 9)[/tex]
[tex]m = \frac{9 - 1}{-3 + 7}[/tex]
-Solve:
[tex]m = \frac{9 - 1}{-3 + 7}[/tex]
[tex]m = \frac{8}{4}[/tex]
[tex]m = 2[/tex]
After you have found the slope, use the slope [tex]2[/tex] and the first point [tex](-7, 1)[/tex] for the Point-Slope Formula:
[tex]y - y_{1} = m (x - x_{1})[/tex]
-Apply them for the formula:
Slope = [tex]2[/tex]
First point = [tex](-7, 1)[/tex]
[tex]\boxed {y - 1 = 2 (x + 7)}[/tex]